Biopesticides manual : guidelines for selecting, sourcing, producing and using biopesticides for key pests of tobacco /: guidelines for selecting, sourcing, producing and using biopesticides for key pests of tobacco. (2018) - Holmes, Keith (Keith Andrew), 1965-
No abstract available